Implementing Tool-Supported Rehearsals for Ambitious Science Teaching in an Elementary Science Methods Classroom - Benedict-Chambers, Amanda; Aram, Roberta; Wood, Gina (Innovations in Science Teacher Education, 2016)
In this article, we focus on the implementation in our elementary science methods course of a suite of tools supporting peer rehearsals designed to provide opportunities for preservice teachers to notice and analyze important features of ambitious science instruction prior to teaching in elementary classrooms. The tools include (1) an Engage-Explore-Explain (EEE) Framework for Science Teaching and Learning, which is similar to the first three phases of the 5E learning cycle (2) a list of Developing Student Ideas targeting science concepts in the lessons (3) a list of Common Challenges to Scientific Practices often experienced by elementary science learners; and (4) a EEE Framework feedback form. In rehearsals, novices use the tools to teach specific ambitious practices to their peers and the teacher educator. As the novices elicit and support students’ thinking, the peers and teacher educator use the tools to determine how to respond in ways that reflect children’s sensemaking and use of scientific practices. We developed the tools to guide novices in (a) designing lessons that engaged elementary students in sensemaking about natural phenomena using scientific practices; (b) anticipating, eliciting, and constructively responding to student ideas during instruction; and (c) reflecting on important features of their own science instruction. We describe the learning opportunities tool-supported rehearsals provide for novices to try out and collectively analyze moves for supporting students’ sensemaking. We also discuss how the just-in-time coaching from teacher educators and peer feedback may develop novices’ pedagogical content knowledge and prepare them to engage children in ambitious practice in elementary school classrooms.